2019
DOI: 10.1186/s13034-019-0275-2
|View full text |Cite
|
Sign up to set email alerts
|

Sibling relationships of female adolescents with nonsuicidal self-injury disorder in comparison to a clinical and a nonclinical control group

Abstract: BackgroundAdolescents’ nonsuicidal self-injury (NSSI) leads to distress that affects the whole family system, and siblings are reported to suffer from disrupted family communication and functioning. So far, no studies have examined the quality of relationships between adolescents with NSSI and their siblings. The aim of the present study was to examine the sibling relationship quality of adolescents with NSSI, adolescents with other mental disorders without NSSI (clinical controls, CC), and adolescents without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 66 publications
2
11
0
1
Order By: Relevance
“…The behavior/environment model summed up some external factors affecting the onset of adolescents' NSSI behavior, and emphasized the role of family environment, adverse life events and peer influence. In line with the model, prior work also have demonstrated the family relationship, peer victimization of teenagers had a great impact on NSSI [15,16] . Parent connectedness is a protective factor for adolescents with NSSI [17] .…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…The behavior/environment model summed up some external factors affecting the onset of adolescents' NSSI behavior, and emphasized the role of family environment, adverse life events and peer influence. In line with the model, prior work also have demonstrated the family relationship, peer victimization of teenagers had a great impact on NSSI [15,16] . Parent connectedness is a protective factor for adolescents with NSSI [17] .…”
Section: Introductionsupporting
confidence: 66%
“…"I think my child has a more introverted personality…" (Participant 2,8,10,11,13,14,15,16,17) "They haven't loved to make friends since they were young. No matter how much I want them to make friends, they don't do it."…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of only child adolescents with NSSI behaviours in the duringpandemic group was only 24.1%, which was significantly lower than that in the pre-pandemic group. Most of them had to suffer the role of taking care of their younger siblings, and according to a related study, it was found that these adolescents might consider caring for young siblings to be stressful, and had the feeling of deprived love from their parents (44,45), which might further lead to NSSI behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Guilt for adolescents who selfinjure also emerges from bad sibling relationships. Tschan, Ludtke, Schmid, & In-Albon (2019) stated that self-injurers have less warmth, less empathy, and more enmity with siblings. Besides, he or she also has weak emotional ties, does not care enough, and rarely gets along with his siblings.…”
Section: Discussionmentioning
confidence: 99%